Evaluation of the School of Library and Information Studies' academic advising based on the undergraduate students' perspectives - Daria, Kriezel Joy R. (2012)
Academic advising in the college is a dynamic process that assists the youth into developing sound decisions that would positively affect their academic and life career. With the issues of multiple academic concentrations available for a Library and Information Science student and the decreasing number of enrollees and graduates in SLIS, the research has been conducted to evaluate the current system of academic advising in the college. The study aimed to find out whether the advising process is perceived effective or not by the undergraduate SLIS students for the 2nd semester of academic year 2011-2012. Specifically, the study determined the advising needs of the three groups of students - original, shiftees and transferees, and their levels of satisfaction. Also, the research identified the strengths and weaknesses of the current advising system. Recommendations were made available towards the end of the study.